Preparation of surface-modified electrode of copper(ii) oxide mixed with the molecularly imprinted polymer for enhancement of melamine detection with photoelectrochemical technique - Dalawan Limthin; Piyawan Leepheng; Benchapol Tunhoo; Korakot Onlaor; Annop Klamchuen; Darinee Phromyothin; Thutiyaporn Thiwawong (My University, 2023)
Melamine contamination in food and beverages affects short- and long-term health. In this work, enhanced sensitivity and selectivity in photoelectrochemical determination for melamine detection was achieved using copper(ii) oxide (CuO) combined with a molecularly imprinted polymer (MIP). A CuO nanomaterial was used to achieve MIP surface modification
Keywords: Molecularly imprinted polymer; Copper oxide; Surface Modification; Melamine detection and toxicity